(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current situation of medication use and treatment awareness among gout patients at Transport Hospital in 2024. Methods: A cross-sectional descriptive study was conducted on 53 inpatients diagnosed with gout at the Department of Internal Medicine 2, Transport Hospital, from March 2024 to December 2024. Patients were enrolled if they met the diagnostic criteria for gout according to Bennett and Wood (1968) and/or EULAR (2015). A convenient sampling method was applied. Results: The majority of participants were male (86.8%), with a mean age of 67.0 ± 16.0 years; notably, 60.4% were aged 70 years or older. Chronic gout or acute flares of chronic gout accounted for 71.7% of cases, with clinical manifestations predominantly involving 1-2 joints (73.6%), primarily in the lower extremities (88.7%), and the first metatarsophalangeal joint being affected in 41.5%. Regarding medication use, 43.4% of patients had self-medicated prior to hospital admission, mainly through over-the-counter drug purchases (65.2%). Self-medication without follow-up was reported in 34.6% of patients, while only 15.4% adhered to scheduled follow-up visits. Awareness of treatment strategies remained limited, particularly concerning the use of urate-lowering therapies (15.1%) and the importance of regular serum uric acid monitoring (26.4%). Conclusion: Medication use and treatment awareness among gout patients remain suboptimal, particularly regarding long-term management. The high rates of self-medication, poor follow-up adherence, and limited understanding of uric acid control underscore an urgent need to strengthen patient counseling, health education, and the development of sustainable follow-up strategies in clinical practice.